Cross-border CBDC Implications on Cournot Banks - Lin, Wiraphat; Wattanakoon, Panit (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2025)
This paper studies the effect of cross-border Central Bank Digital Currencies (CBDC) on the Cournot domestic banking landscape and its effect on financial stability. A simple open economy version of the classical model of bank runs, augmented with a credible and remunerated foreign CBDC, is employed. The first part of the paper investigates the effect of domestic banks’ market power without foreign CBDC. We find that though some bank market powers cause the economy to have lower welfare than the social planner, it has higher welfare than perfect competition. Market-power-enhanced banks can internalize pecuniary externalities from asset price changes and generate more welfare than perfect competition. The second part is the introduction of crossborder foreign CBDC as an international safe asset. We find that the foreign CBDC causes capital outflow and increases the risk of financial disintermediation.